Gellner's genealogy of the open society: Biopolitics as fragment and remainder. (June 2015) - Ryan, Kevin
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner's writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner's method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.